Analisis Indeks Kepuasan Masyarakat terhadap Pelayanan Publik pada Pusat Kesehatan Masyarakat Langsa Barat - Syardiansah, Syardiansah (Universitas Medan Area, 2019)
Langsa Barat Health Center is a first-rate health facility that provides health services to the community. In providing health services to the community, all existing service units and all employees are committed to providing quality health care and care for the safety of patients, visitors, communities and employees. Service standards are a commitment of service providers to provide services with a certain quality determined on the basis of a combination of community expectations and the ability of service providers. Establishment of service standards through identification of service type, identification of service type, customer identification, customer expectation identification, vision and service mission formulation, process and procedure analysis, facilities and infrastructure, time and cost of service.To set the standard of service whether or not a reference is used from the Decree of the Minister of Administrative Reform Number KEP / 25 / M.PAN / 2/2004 on general guidelines for the preparation of public satisfaction index. Where is the location of this research is Puskesmas Langsa Barat. This study aims to determine the index of community satisfaction with public services at the Langsa Barat Health Center. The respondents in this study were the health service users in Langsa Barat Health Center.Based on the result of the research, it is found that service indicator is in the form of officer discipline, officer responsibility, courtesy and officer friendliness, suitability of cost with specified, and service unit comfort have excellent service quality. While other indicators have good service quality. And overall the index of community satisfaction on public services at Langsa Barat Health Center has good quality of service.